Pengaruh Etika Moral dalam Pembentukan Karakter Mahasiswa Prodi Manajemen Informasi Kesehatan STIKes Santa Elisabeth Medan - Rezekieli Zebua; Malvin Jaya Gulo; Vivian Eliyantho Gulo; Jatmika Harefa; Tahoma Siahaan (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Ethics is a collection of principles, values, or morals that guide a person in behaving. Ethics is also concerned with good and bad things in behavior in which there are moral rights and obligations of a person in social life. Ethics is used to decide what is right in a given situation so as to decide what is consistent with existing value systems in individuals and organizations. In the world of education, it is expected that every student demonstrates all ethical actions so as to provide a good assessment of the people around him. The character and morals of students need to be grown to the maximum, so that students will not only excel in the academic field, but also excel in the non-academic field to support self-identity in the midst of globalization. The purpose of this study was to determine the effect of moral ethics on the education and character of students in the Health Information Management study program. The population used was all students of MIK Level 2 at Stikes Santa Elisabeth Medan with a sample of 17 people. This type of research is descriptive research. The instrument used is a questionnaire. Descriptive data analysis. The results showed that students of Health Information Management Study Program level 2 with a good level of moral ethics (76.5%), 17.6% enough, and not good (5.9%). Based on gender 41.2% were male and 58.8% were female. After conducting research on Health Information Management students at the STIKes Santa Elisabeth Campus, Medan, it can be concluded that the level of moral ethics of MIK level 2 students is said to be good (76.5%) because they can apply ethical behavior and respect for each other in the campus environment.